THERAPEUTIC EFFECTS OF HIGH FREQUENCY ELECTROMAGNETIC RADIATION AND ULTRASOUND ON INTERSTITIAL INFLAMMATION AND PROXIMAL TUBULAR DIAMETER IN KIDNEYS OF CHICK EMBRYO EXPOSED TO ADVANCED ELECTROMAGNETIC RADIATION (WI-FI) - Iftikhar, Zubia; Qamar, Khadija; Zakria, Iram; Akhtar, Noreen; Abaid, Mehwish; Zahid, Aqsa (Pakistan Armed Forces Medical Journal, 2020)
Objective: To assess the ameliorative effects of therapeutic ultrasound and high frequency electromagnetic radiation on inflammation and proximal convoluted tubular diameter, after damage induced by wireless fidelity, on kidneys of chick embryo. Study Design: Laboratory based experimental study. Place and Duration of Study: Department of Anatomy, Army Medical College, in collaboration with Armed Forces Institute of Rehabilitation Medicine Rawalpindi, from May to Jun 2019. Methodology: Forty day “0” eggs of Fayomi breed weighing 48-50 grams were divided into four groups. Group A served as a control group while group B, C and D were the experimental groups exposed to wireless fidelity for 30 minutes daily for 15 days. Group C was further given therapeutic ultrasound while group D received high frequency electromagnetic radiation in the form of microwave diathermy. Results: Therapeutic ultrasound and high frequency electromagnetic radiations both improved the interstitial inflammation (p-value <0.001 on intergroup comparison), and proximal tubular diameter (group A = 59.52 ± 4.55µm, group B = 75.48 ± 1.32µm, group C, = 61.15 ± 2.71µm, group D = 56.15 ± 1.94µm; p-value <0.001. Conclusion: Therapeutic ultrasound and high frequency electromagnetic radiation had ameliorative effects in reverting derangements induced by Wi-Fi in kidneys of chick embryo with HF-EMR being superior to ultrasound.